Architecture of rod and cone circuits to the on-beta ganglion cell - Sterling, P (J Neurosci, 1988)
Photoreceptors connect to the on-beta ganglion cell through parallel circuits involving rod bipolar (RB) and cone bipolar (CB) neurons. We estimated for a small patch in the area centralis of one retina the 3- dimensional architecture of both circuits. This was accomplished by reconstructing neurons and synapses from electron micrographs of 189 serial sections. There were (per mm2) 27,000 cones, 450,000 rods, 6500 CBb1, 30,300 RB, 4100 All amacrines, and 2000 on-beta ganglion cells. The tangential spread of processes was determined for each cell type, and, with the densities, this allowed us to calculate the potential convergence and divergence of each array upon the next. The actual numbers of cells converging and diverging were estimated from serial sections, as were the approximate numbers of chemical synapses involved. The cone bipolar circuit showed narrow convergence and divergence: 16 cones----4 CBb1----1 on-beta 1 cone----1 CBb1----1.2 on- beta This circuit is thought to contribute significantly to the on-beta cell's photopic receptive field because the CBb1 has a center-surround receptive field whose center diameter is greater than the spacing between adjacent CBb1s. Consequently, the receptive fields of the CBb1s converging on a beta cell are probably largely concentric and thus mutually reinforcing in their contributions to the on-beta. The rod bipolar circuit showed a wider convergence and divergence: 1500 rods---- 100 RB----5 AII----4 CBb1----1 on-beta 1 rod----2 RB----5 AII----8 CBb1- ---2----2 on-beta The 1500 rods converging via this circuit account for the spatial extent of the beta cell's dark-adapted receptive field. This convergence also accounts for the ganglion cell's maintained discharge, which is thought to arise from about 6 quantal “dark events” per second. This many dark events would appear in the ganglion cell if each rod in the circuit contributed 0.004 dark events per second, and this is close to what has been measured in monkey rods (Baylor et al., 1984). Divergence in this circuit serves to expand the number of copies of the quantal signal (1 rod----8 CBb1) and so to engage large numbers of chemical synapses that provide amplification. Reconvergence at the last stage (8 CBb1----2 on-beta) may reduce (by signal averaging) the synaptic noise that would otherwise accumulate along the pathway.